Ocean acidification increases fatty acids levels of larval fish - Díaz-Gil, Carlos (Biol Lett, 2015)
Rising levels of anthropogenic carbon dioxide in the atmosphere are acidifying the oceans and producing diverse and important effects on marine ecosystems, including the production of fatty acids (FAs) by primary producers and their transfer through food webs. FAs, particularly essential FAs, are necessary for normal structure and function in animals and influence composition and trophic structure of marine food webs. To test the effect of ocean acidification (OA) on the FA composition of fish, we conducted a replicated experiment in which larvae of the marine fish red drum (Sciaenops ocellatus) were reared under a climate change scenario of elevated CO(2) levels (2100 µatm) and under current control levels (400 µatm). We found significantly higher whole-body levels of FAs, including nine of the 11 essential FAs, and altered relative proportions of FAs in the larvae reared under higher levels of CO(2). Consequences of this effect of OA could include alterations in performance and survival of fish larvae and transfer of FAs through food webs.